The Triple χ^3 Sequence Spaces - Ayhan Esi; N. Subramanian (International Journal of Mathematics And its Applications, 2017)
Let χ^3 denote the space of all triple gai sequences and Λ^3 the space of all triple analytic sequences. This paper some theorems on general properties of χ^3 sequences have been established.